Sevoflurane exposure causes neuronal apoptosis and cognitive dysfunction by inducing ER stress via activation of the inositol 1, 4, 5-trisphosphate receptor - Zhang, Qi; Li, Yanan; Wang, Xupeng; Yin, Chunping; Zhou, Qi; Guo, Junfei; Zhao, Juan; Xian, Xiaohui; Hou, Zhiyong; Wang, Qiujun (Frontiers in Aging Neuroscience, 2022)
The role of the inositol 1, 4, 5-trisphosphate receptor (IP3R) in hippocampal neuronal apoptosis and cognitive dysfunction induced by sevoflurane is currently unclear. Therefore, in this study, we investigated the role of the IP3R in endoplasmic reticulum stress and hippocampal neuronal apoptosis induced by sevoflurane in aged rats and isolated hippocampal neurons using both in vivo and in vitro experiments, including bioinformatics, functional enrichment analysis, gene set enrichment analysis, hematoxylin and eosin staining, TUNEL assay, flow cytometry, western blot analysis and transmission electron microscopy. Furthermore, behavioral assessment was performed with the Morris water maze test. We identified 232 differentially expressed genes induced by sevoflurane exposure, including 126 upregulated genes and 106 downregulated genes. Sevoflurane exposure caused cognitive impairment and neuronal injury, and increased p-IP3R levels and ER stress. An IP3R inhibitor, 2-APB, suppressed these changes, while an IP3R agonist, FK-506, aggravated these changes. Together, these findings suggest that sevoflurane exposure causes marked cognitive dysfunction in aged rats and neuronal injury in isolated hippocampal neurons by activating the IP3R and inducing cytoplasmic calcium overload, thereby resulting in endoplasmic reticulum stress and hippocampal neuronal apoptosis.